Effect of holding pressure on densification and mechanical properties of Cf/Mg composites - Wei, X.; Qi, L.; Ju, L.; Tian, W.; Hou, X.; Li, H. (Taylor & Francis, 2016)
Carbon fibre reinforced magnesium alloy matrix composites were fabricated by using liquid–solid extrusion directly following vacuum infiltration technique. The experimental results showed that the microstructures of Cf/Mg composites depended on the holding pressure. The porosity was reduced gradually, and the densification was improved obviously, respectively, with the increase of the holding pressure. The densification, hardness and Ultimate tensile strength of Cf/Mg composites were significantly improved as the holding pressure increased in the range of 0.1–15 MPa. The densification was not obvious, but the UTS of the Cf/Mg composites decreased gradually as the holding pressure increased in the range of 25–45 MPa. The Cf/Mg composites presented a good performance when the holding pressure was about 15 MPa.